2010
DOI: 10.4319/lo.2011.56.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

Coherent patterns in bacterial growth, growth efficiency, and leucine metabolism along a northeastern Pacific inshore‐offshore transect

Abstract: We investigated the patterns in bacterial growth, production, respiration, growth efficiency (BGE), and bacterial leucine respiration and C-to-leucine yield (i.e., conversion factor [CF]) along a transect off the coast of Oregon. Plankton respiration along the transect averaged 1.15 6 0.16 mg C L 21 h 21 , peaking in the coastal upwelling region. The respiration in the filtered fraction, which was dominated by bacterial biomass, accounted for 79% of the total respiration. The different approaches that we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 63 publications
10
92
2
Order By: Relevance
“…Since then, the vast majority of studies still corroborate this pattern: BGE >30% on average in more productive areas, such as upwelling and estuarine systems (ASMALA et al, 2014;NEWELL, 2012;FUENTES et al, 2012;GUENTHER et al, 2008), and BGE < 20% on average at oceanic sites (ALONSO-SÁEZ et al, 2007;DEL GIORGIO et al, 2011;LØNBORG et al, 2013;. This means that in most eutrophic systems, bacterioplankton act more as a source of organic carbon for the higher consumers.…”
Section: Introductionsupporting
confidence: 49%
“…Since then, the vast majority of studies still corroborate this pattern: BGE >30% on average in more productive areas, such as upwelling and estuarine systems (ASMALA et al, 2014;NEWELL, 2012;FUENTES et al, 2012;GUENTHER et al, 2008), and BGE < 20% on average at oceanic sites (ALONSO-SÁEZ et al, 2007;DEL GIORGIO et al, 2011;LØNBORG et al, 2013;. This means that in most eutrophic systems, bacterioplankton act more as a source of organic carbon for the higher consumers.…”
Section: Introductionsupporting
confidence: 49%
“…del Giorgio et al (2011) measured BGE of just 13% 6 1% in the Pacific Ocean and concluded their research by stating that ''the patterns in C consumption, growth, BGE and leucine metabolism all reflect the basic physiological response of bacteria to energy limitation due to high maintenance costs associated with life in oligotrophy.'' Yet in this study ''maintenance costs'' are perhaps considerably less since bacterioplankton in surface waters of the open Atlantic Ocean are dominated by SAR11 and Prochlorococcus (Morris et al 2002;Heywood et al 2006), which evolved streamlined genomes (Giovannoni et al 2005;Kettler et al 2007) but kept and express numerous ABCtype transporters (Sowell et al 2008) and exercise photoheterotrophy (Mary et al 2008a;Gó mez-Pereira et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between this and previous studies may in part be methodological. For instance, acidification of samples before filtration (Hobbie and Crawford 1969;Crawford et al 1974;Alonso-Sáez et al 2007;del Giorgio et al 2011) could potentially compromise cell integrity and lead to loss of material during filtration or centrifugation, leading to an underestimation of assimilation rate and hence overestimation of respiration as a percentage of total consumption. However, the biggest influence is most likely the concentration of 14 Cleucine applied to samples.…”
Section: Discussionmentioning
confidence: 99%
“…Details of these oligo-and mesotrophic environments (up to 3.4 mg chlorophyll l À 1 ) have been already published: NOR , NAT (González et al, 2000), COC (Alonso-Sáez et al, 2007), WE (del Giorgio et al, 2011), BL (Alonso-Sáez et al, 2008, AL (Arin et al, 2002), IND and DH (Díez et al, 2004). Seawater was taken with Niskin bottles attached to a CTD (conductivity, temperature, depth recorder) rosette, prefiltered by a 200-mm nylon mesh and then filtered in succession through a 3-mm pore-size polycarbonate filter and a 0.2-mm pore-size Sterivex unit (Durapore, Millipore, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%